Mechanisms for Implementing Sustainable Green Economy In The Field Of Tourism in Ayla Oasis / Aqaba City - Almahasneh, Mohammad Fadel Salman; Rawashdeh, Osama Mohammad; Alkhzalah , Shaker; Abulaila , Hanadi Lutfi (Journal of Ecohumanism, 2025)
The tourism industry is one of the important sectors on which many countries depend for economic growth and development, as it is one of the sources of foreign exchange, and with the increase in tourists around the world, some tourism activities harmful to the environment appeared, which resulted in the emergence of some trends that stimulate tourism to preserve the environment, the most important of which are the trends that require the need to transform the tourism sector into a green economy. The study aimed to: To identify the reality of tourism in Ayla Oasis / Aqaba City, and to reveal the mechanisms of activating the sustainable green economy in the field of tourism in Ayla Oasis / Aqaba City: The descriptive method, and the researcher designed a questionnaire: It consisted of two axes with a total of (31) phrases, under the first axis (13) phrases, and under the second axis: (18) phrases. The most important findings are: Apartments are sustainable accommodations that provide tourists with stunning views of the sea; Ayla’s yacht marina is a venue for hosting boats from foreign countries as part of their global tourist tours; supporting projects that focus on protecting the environment to incentivize tourists to be attracted to it; and supporting projects that focus on protecting the environment. Improving infrastructure such as public transportation, hotels, etc. in line with the requirements of green tourism, and the importance of taking the necessary measures to improve air and water quality in tourist areas to maintain the comfort of tourists.